Protein Toxin Chaperoned by LRP‐1‐Targeted Virus‐Mimicking Vesicles Induces High‐Efficiency Glioblastoma Therapy In Vivo. Issue 30 (11th June 2018) - Jiang, Yu; Yang, Weijing; Zhang, Jian; Meng, Fenghua; Zhong, Zhiyuan
Abstract: Glioblastoma is a most intractable and high‐mortality malignancy because of its extremely low drug accessibility resulting from the blood–brain barrier (BBB). Here, it is reported that angiopep‐2‐directed and redox‐responsive virus‐mimicking polymersomes (ANG‐PS) (angiopep‐2 is a peptide targeting to low‐density lipoprotein receptor‐related protein‐1 (LRP‐1)) can efficiently and selectively chaperone saporin (SAP), a highly potent natural protein toxin, to orthotopic human glioblastoma xenografts in nude mice. Unlike chemotherapeutics, free SAP has a low cytotoxicity. SAP‐loaded ANG‐PS displays, however, a striking antitumor activity (half‐maximal inhibitory concentration, IC50 = 30.2 × 10 −9 m ) toward U‐87 MG human glioblastoma cells in vitro as well as high BBB transcytosis and glioblastoma accumulation in vivo. The systemic administration of SAP‐loaded ANG‐PS to U‐87 MG orthotopic human‐glioblastoma‐bearing mice brings about little side effects, effective tumor inhibition, and significantly improved survival rate. The protein toxins chaperoned by LRP‐1‐targeted virus‐mimicking vesicles emerge as a novel and highly promising treatment modality for glioblastoma. Abstract : Angiopep‐2 (ANG)‐directed and redox‐responsive virus‐mimicking polymersomes efficiently and selectively deliver saporin (SAP), a potent natural protein toxin, to human glioblastoma engrafted in the brain of nude mice, leading to effective tumor suppression and significantly improved survival rate with little adverse effects.